Quantification of the Role of Teupol® 25P and Graminex® G96 Compared to Hexanic Extract of Serenoa repens in Patients Affected by Lower Urinary Tract Symptoms During Treatment with Silodosin - Yazan Al Salhi; Damiano Graziani; Andrea Fuschi; Fabio Maria Valenzi; Manfredi Bruno Sequi; Paolo Pietro Suraci; Alice Antonioni; Onofrio Antonio Rera; Cosimo De Nunzio; Riccardo Lombardo; Paolo Benanti; Giuseppe Candita; et al. (Medicina, 2025)
Background and Objectives: While α1-blockers like silodosin are the mainstay for treating lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH), combination therapy with phytotherapeutics may provide enhanced symptom control. Xipag® is a novel formulation containing Graminex® G96 (pollen extract) and Teupol® 25P (teupolioside), offering anti-inflammatory and antiandrogenic effects. This study aimed to evaluate the efficacy of Xipag® versus hexanic extract of Serenoa repens (HESr), both in combination with silodosin, in patients with LUTS/BPH. Materials and Methods: We conducted a single-center, prospective, observational, comparative study involving male patients with moderate-to-severe LUTSs undergoing treatment with silodosin. Patients were allocated to receive either Xipag® or HESr in addition to silodosin, with follow-up every 3 months for 12 months. Primary outcomes included changes in symptom scores such as IPSS, QoL, and functional improvements such as peak urinary flow rate (Qmax). Multivariable regression analyses were used to assess predictors of the response. Results: Patients receiving Xipag® showed significantly greater improvements in Qmax at all follow-up points (p < 0.05), with earlier and more sustained benefits compared to the HESr group. QoL index scores and PSA levels were also significantly better in the Xipag® group starting from month six onward. IPSS scores improved in both groups but were significantly lower in the Xipag® group only at 12 months (p = 0.04). No differences in erectile function (IIEF-5) or adverse events were observed. Conclusions: Xipag® in combination with silodosin provides superior improvement in urinary flow, symptom-related QoL, and PSA reduction compared to HESr plus silodosin, with a favorable safety profile. These findings support the use of multi-target nutraceuticals like Xipag® as a valuable adjunct in the management of LUTS/BPH. Larger randomized trials are warranted to confirm these results and explore underlying mechanisms.